Reflections on the 2024 AMR Decade Award: Zooming Out and Zooming In to Expand Research on Multiple Institutional Logics and Organizational Hybridity - Besharov, Marya; Smith, Wendy K. (Academy of Management Review, 2025)
Scholarship on multiple institutional logics and organizational hybridity has exploded since we published our 2014 paper, “Multiple Institutional Logics in Organizations: Explaining Their Varied Nature and Implications.” We revisit that paper’s origins, explore the research that built on the paper over the last decade, and offer provocations for future scholarship. Revisiting the development of our paper, we highlight multiple research tensions—between breadth and depth, focus and expansion, theoretical contribution and practical impact, rigor and relevance—and unpack how navigating those tensions impacted the paper. Exploring key developments in multiple logics and hybridity research over the last decade, we note advances in dimensions of variation, antecedents and consequences, and attention to dynamism and change. Provoking future scholarship, we invite researchers to both zoom out, adopting systems perspectives to unpack the complexity of hybridity amid intertwined global challenges, and to zoom in, embracing a practice ontology to examine the active work in navigating, enacting, and shaping competing demands in organizations. Together, zooming out and zooming in can help scholars continue advancing a research agenda on logics and hybridity that is theoretically robust, empirically rich, and practically responsive to the demands of a complex and uncertain world.